Development of a consensus approach for return of pathology incidental findings in the Genotype-Tissue Expression (GTEx) project. Issue 9 (14th June 2018) - Lockhart, Nicole C; Weil, Carol J; Carithers, Latarsha J; Koester, Susan E; Little, A Roger; Volpi, Simona; Moore, Helen M; Berkman, Benjamin E
Abstract : The active debate about the return of incidental or secondary findings in research has primarily focused on return to research participants, or in some cases, family members. Particular attention has been paid to return of genomic findings. Yet, research may generate other types of findings that warrant consideration for return, including findings related to the pathology of donated biospecimens. In the case of deceased biospecimen donors who are also organ and/or tissue transplant donors, pathology incidental findings may be relevant not to family members, but to potential organ or tissue transplant recipients. This paper will describe the ethical implications of pathology incidental findings in the Genotype-Tissue Expression (GTEx) project, the process for developing a consensus approach as to if/when such findings should be returned, possible implications for other research projects collecting postmortem tissues and how the scenario encountered in GTEx fits into the larger return of results/incidental findings debate.